Molecular basis of longevity sustaining characteristics of Chinese medicine herbs - Qianqian Wang; Ying Hu; Liangxia Jiang; Bing Guo; Ying Luo (Elsevier, 2022)
The balancing between tumor suppression and cell viability is the key to balance aging and tumorigenesis, and reach tumor-free longevity, or healthy aging. We speculate that the balance of tumor suppression signaling and the cell growth sustaining mechanisms in molecular genetics might reflect the balance between Yin and Yang in Chinese medicine. Some Chinese medicine herbs are known to sustain longevity, and help to prevent aging related diseases, such as Panax Ginseng, Ganoderma Lucidum etc. Based on Chinese medicine databases and the molecular signature database, we try to apply in silico systems pharmacology to analyze the function of these herbs in modulating signaling pathways. We found that most of these herbs could enhance cellular mitochondrial function: oxidative phosphorylation. Surprisingly, the lipids metabolism pathways were found in all the herbs analyzed. Interestingly, the cell proliferation pathways, such as telomere maintenance pathway, Myc pathway, E2F pathway, as well as the cell quality control pathway (apoptosis pathway) were also found to be enhanced in most herbs, which added evidences to our balancing hypothesis. Thus, our data revealed the sustainable energy production, the sustainable cell proliferation, and the quality control build the life triangle for the mechanism of action of Chinese medicinal herbs with longevity sustaining property. This methodology might help to predict the molecular mechanism of Chinese medicine herbs, and further understand the formulation of Chinese medicine in preventing aging-related diseases. The limitations of this kind of analysis are also discussed.